2020
DOI: 10.22541/au.159069206.66900218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energetic Costs of Cognitive Abilities: Testing the Expensive Tissue Hypothesis

Abstract: Enlarged brains of homeotherms bring behavioural advantages, but incur high energy expenditures for the animal. The 'Expensive Tissue' (ET) hypothesis links the evolution of the enlarged brain to increased cognitive abilities (CA) that improved foraging performance, social interactions and allowed for reduction in size of the energetically demanding gut. We tested the directionality of the evolutionary trade-off between brain, gut and CA using experimental evolution model consisting of lines of laboratory mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The emergence of hominin meat-eating is also coeval with the earliest stone tool use 16 , 17 . This has also been used to controversially argue that such a dietary change played a crucial role in early hominin cognitive evolution 8 , 12 , 18 . Behaviorally, meat acquisition strategies have also been controversial because they impact our perception of how complex human behaviors emerged 1 , 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of hominin meat-eating is also coeval with the earliest stone tool use 16 , 17 . This has also been used to controversially argue that such a dietary change played a crucial role in early hominin cognitive evolution 8 , 12 , 18 . Behaviorally, meat acquisition strategies have also been controversial because they impact our perception of how complex human behaviors emerged 1 , 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The study of Opsanus tau shows that increased investment in one structure does not necessarily drive a loss of mass in one or more organs (Dornburg et al, 2018). Studies in mice have shown that evolutionary increase in cognitive abilities was initially associated with brain plasticity and fueled by an enlarged gut, which was not traded off for brain size, as the ETH posits (Konarzewski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%